Calidad de servicio y su relación con la satisfacción de los clientes de la Lavanderia Hoy Lavo Yo, Iquitos 2023 - Angulo Tina, Marjorie Isabel (2023)
The study conducted at "Hoy Lavo Yo" Laundry in Iquitos in 2023 aimed to establish the connection between service quality and customer satisfaction. Employing a descriptive correlational method, a significant correlation of 0.838** was identified between these two variables. The findings by Espinal and Palomino consistently underscored the importance of service quality for customer satisfaction. These results are supported by Díaz, who identified a strong association between water service management and user satisfaction in Lurín. Regarding the first objective, both Aguirre and Torres emphasized the link between reliability and satisfaction, with differences in the magnitude of influence. Similarly, for the second objective, Torres concurred with our findings about responsiveness. In the third objective, security proved to be relevant, backed by Aguirre and Torres. Concerning the fourth objective, empathy influenced user satisfaction, supported by Aguirre and Torres. Lastly, tangible aspects also played a role, supported by Aguirre and Torres. Collectively, these results underline the significance of the continuous improvement process in service quality across multiple aspects to enhance customer satisfaction at "Hoy Lavo Yo" Laundry.